Aplicação dos novos critérios para Cancro da Tiróide Diferenciado de Alto Grau numa série de cancro da tiróide recorrente: um estudo retrospetivo de 138 casos. - Mariana Costa Caldeira (2024)
In the latest 5th WHO's Classification of Tumors of Endocrine Organs, a new term was created to identify those cases, at the time of pathological evaluation, which have a worse prognosis within differentiated follicular cell-derived thyroid carcinomas (DFCDTC): Differentiated High Grade Thyroid Carcinoma (DHGTC). In our work, we aimed to evaluate its frequency and clinicopathological features within a series of recurrent DFCDTC. We gathered several clinicopathological characteristics of a retrospective cohort of 138 patients with primarily resected thyroid cancer which recurred after total thyroidectomy and adjuvant radioiodine therapy. We also reclassified them as DHGTC according to 5th WHO's criteria; compared DHGTC to non-high grade differentiated follicular cell-derived thyroid carcinomas (non-HG-DTC) and described the clinical behavior and pathological features of thyroid cancer with radioactive iodine refractoriness (RAIR). We found that DHGTC's prevalence is higher than what is described in studies without prior clinical selection. In comparison to non-HG-DTC, DHGTC cases were significantly associated to several adverse clinicopathological features: higher tumor size; tall-cell subtype of PTC; mitotic index ≥5; tumor necrosis; lymphovascular invasion; high AJCC 8th edition pT stage; distant metastasis; lung metastasis; synchronous metastasis and persistence of disease at the end of follow-up. Furthermore, the number of cases which developed RAIR (n=12 [8,7%]), despite low, is quite significant, as the estimated incidence of these forms of cancer is of 4-5 cases/year/million people, and we described their clinicopathological characteristics. Our results strengthen the clinical usefulness of DHGTC classification by indicating patients at a higher risk for progression and highlight the need for tight surveillance in these forms of cancer.